Cryptic activation of an Irf8 enhancer governs cDC1 fate specification - Durai, Vivek; Bagadia, Prachi; Granja, Jeffrey M.; Satpathy, Ansuman T.; Kulkarni, Devesha H.; Davidson, Jesse T.; Wu, Renee; Patel, Swapneel J.; Iwata, Arifumi; Liu, Tian-Tian; Huang, Xiao; Briseno, Carlos G.; et al. (Nature Immunology, 2019)
Induction of the transcription factor Irf8 in the common dendritic cell progenitor (CDP) is required for classical type 1 dendritic cell (cDC1) fate specification, but the mechanisms controlling this induction are unclear. In the present study Irf8 enhancers were identified via chromatin profiling of dendritic cells and CRISPR/Cas9 genome editing was used to assess their roles in Irf8 regulation. An enhancer 32 kilobases (kb) downstream of the Irf8 transcriptional start site (+32-kb Irf8) that was active in mature cDC1s was required for the development of this lineage, but not for its specification. Instead, a +41-kb Irf8 enhancer, previously thought to be active only in plasmacytoid dendritic cells, was found to also be transiently accessible in cDC1 progenitors, and deleting this enhancer prevented the induction of Irf8 in CDPs and abolished cDC1 specification. Thus, cryptic activation of the +41-kb Irf8 enhancer in dendritic cell progenitors is responsible for cDC1 fate specification.
Created from Fastlane, Scopus look-up